Increasing Student Competency Through Catia V5 Software Training - Sulistiyanto, Muchlis; Nurhidayah, Siti; Basri, Hasan; Khoiriyah, Ummi; Putrianika, Puput; Widyowati, Dian Desty; Zhafiraah, Nazma Riska (Entrepreneurship and Community Development, 2023)
The current era demands that all aspects of engineering be carried out automatically, including creating technical drawings, which were previously done manually, now being replaced with drawings using CAD (Computer Aided Design) software, which offers automatic drawings. This problem impacts the industrial world, which requires skilled workers in the field of design. In the manufacturing industry, Catia V5 is widely used in product designs because it is faster and easier to use than paper and drawing tools. This Catia V5 Software training aims to improve students' 2D and 3D drawing abilities. This activity was done online in 6 meetings via the Zoom Meeting application. The impact of the success of this program is in the form of increasing students' knowledge and understanding of 2D and 3D sketching via Catia V5 and being able to operate the features of Catia V5.